キタハンキュウ チュウ コウイド ニ オケル リュウカ カルボニル (COS) ノ ノウド ノ イド ブンプ - 猪股, 弥生; イノマタ, ヤヨイ; 松永, 捷司; マツナガ, カツジ; 長田, 和雄; オサダ, カズオ; 渡辺, 征春; ワタナベ, マサハル; 岩坂, 泰信; イワサカ, ヤスノブ; Inomata, Yayoi; Matsunaga, Katsuji; et al. (2002)
P(論文) 北極航空機観測（AAMP 98）において，北半球中・ 高緯度上空の対流圏・下部成層圏で大気試料を採取し，硫化カルボニル（COS）の濃度を測定した. 53°N以北の対流圏における COS濃度は378–433 pptvの範聞でほぼ一 定の濃度分布であり，緯度による濃度差は認められなかった．二硫化炭素（CS2）の濃度が非常に低いことから，53°N以北の大気中ではCS2の光化学反応によって付加されるCOS量は少ない可能性が示唆された． 高度12 kmにおける下部成層圏のCOSの平均濃度は対流圏内の濃度と比較して低いことが認められた．しかし，圏界面に対して1–2 km 高い領域ではCOS濃度は高度が高いほど濃度が減少する傾向が非常にわずかに認められたにすぎない．このことから，極夜明け直後の下部成層圏では光化学反応による COS濃度の減少は非常に 少ないものと推察された． Concentrations of COS in the stratosphere and troposphere were determined from grab samples collected at altitudes ranging from 0.3–12 km during an aircraft flight over mid-high latitude in the Arctic Airborne Measurement Program 1998 (AAMP 98). Concentrations of COS in the troposphere were almost constant within the range of 378-433 pptv. Taking into account the lower abundance of CS2, the photochemical production of COS from CS2 oxidation was less for atmospheric COS north of 53°N. In the stratosphere below 12 km altitude, average concentrations of COS were lower than those in the troposphere. However, concentrations of COS decreased with increasing altitude 1–2 km above the tropopause. It is thought that the phototchemical oxidation of COS in the lowest part of the stratosphere was less during the observation period. departmental bulletin paper